2017
DOI: 10.1016/j.icarus.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Possibility of microscopic liquid water formation at landing sites on Mars and their observational potential

Abstract: Microscopic liquid brines, especially calcium-perchlorate could emerge by deliquescence on Mars during night time hours. Using climate model computations and orbital humidity observations, the ideal periods and their annual plus daily characteristics at various past, current and future landing sites were compared. Such results provide context for future analysis and targeting the related observations by the next missions for Mars. Based on the analysis, at most (but not all) past missions' landing sites, micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Gough et al (2016) analysed the formation of liquid water via the deliquescence of calcium chloride at low temperatures and concluded that calcium chloride may help to form liquid water that could cause slope streaks on Mars. Pál and Kereszturi (2016) also predicted the appearance of microscopic amount liquid water on the hygroscopic mineral surfaces on Mars.…”
Section: Water On Earth and Other Terrestrial Planetsmentioning
confidence: 87%
“…Gough et al (2016) analysed the formation of liquid water via the deliquescence of calcium chloride at low temperatures and concluded that calcium chloride may help to form liquid water that could cause slope streaks on Mars. Pál and Kereszturi (2016) also predicted the appearance of microscopic amount liquid water on the hygroscopic mineral surfaces on Mars.…”
Section: Water On Earth and Other Terrestrial Planetsmentioning
confidence: 87%
“…Several climate models favor a wet but cold surface on early Mars [ 29 ], on which the volumetric and temporal occurrence of liquid water markedly decreased [ 30 ]. Thus, during most of Martian history, only microscopic liquid water (e.g., microscopic liquid brines) may have been present [ 31 , 32 ], though chemical alteration involving perchlorate brines and microscopic liquid films may have been common [ 33 , 34 ]. Importantly, ultraviolet and ionizing radiation can degrade biosignatures at the surface [ 35 ] and subsurface [ 36 ], respectively, and surface oxidizing salts including perchlorate can encourage complete combustion of organic carbon during thermal and evolved gas analysis [ 37 , 38 ], which is currently the only method employed for the detection of organic carbon on Mars.…”
Section: Introductionmentioning
confidence: 99%
“…One of the main goals of Mars investigation is “to follow the water” [ 3 ] as a prerequisite for the survival of living entities. Because of low temperatures (e.g., 215 K to 273 K at the equator) [ 3 ] and low Martian atmospheric pressure (600–800 Pa near the surface) [ 1 ], water can exist only as vapor, as ice, in brines [ 4 ], or bounded on the surface of the regolith as interfacial water in a liquid-like state [ 5 ], and it might also form by the process of deliquescence [ 6 ]. The water vapor is of particular interest, because it influences chemical reactions; because of the water content in the lower atmosphere and upper regolith, the phenomena like fog and thin frost layers occur, and could also be important for potential life forms.…”
Section: Introductionmentioning
confidence: 99%
“…A similar investigation in the regular air of the Earth, performed in the same laboratory, has already been described in the literature [ 8 ]. That former paper [ 6 ] is essential for the understanding of the present paper, because the experimental setup, definitions of parameters, and so on, that are used in the present paper, have been explained and defined in the literature [ 8 ].…”
Section: Introductionmentioning
confidence: 99%